2022
DOI: 10.3390/ijms23084077
|View full text |Cite
|
Sign up to set email alerts
|

In Situ PD-L1 Expression in Oral Squamous Cell Carcinoma Is Induced by Heterogeneous Mechanisms among Patients

Abstract: The expression of programmed death ligand-1 (PD-L1) is controlled by complex mechanisms. The elucidation of the molecular mechanisms of PD-L1 expression is important for the exploration of new insights into PD-1 blockade therapy. Detailed mechanisms of the in situ expression of PD-L1 in tissues of oral squamous cell carcinomas (OSCCs) have not yet been clarified. We examined the mechanisms of PD-L1 expression focusing on the phosphorylation of downstream molecules of epidermal growth factor (EGF) and interfero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The accumulation of gene alterations produced by clonal evolution could result in a cetuximab-resistant MEC clone. Our previous study showed that EGFR signaling in OSCCs reduces effector T-cell infiltration and increases Treg, generating an immunosuppressive tumor microenvironment similar to that observed in non-small cell lung cancers [ 30 , 31 ]. Future investigations should focus on the influence of EGFR signaling blockade on tumor immunity and survival using the MEC cell lines.…”
Section: Discussionmentioning
confidence: 96%
“…The accumulation of gene alterations produced by clonal evolution could result in a cetuximab-resistant MEC clone. Our previous study showed that EGFR signaling in OSCCs reduces effector T-cell infiltration and increases Treg, generating an immunosuppressive tumor microenvironment similar to that observed in non-small cell lung cancers [ 30 , 31 ]. Future investigations should focus on the influence of EGFR signaling blockade on tumor immunity and survival using the MEC cell lines.…”
Section: Discussionmentioning
confidence: 96%
“…An overexpression of NCOA2 in mouse prostate tumors led to the overactivation of PI3K/AKT and MAPK signals, thus promoting the tumor malignancy [ 24 ]. The epidermal growth factor upregulated the PD-L1 expression in OSCC cell lines through the epidermal growth factor receptor (EGFR)/PI3K/AKT pathway [ 25 ]. Ginsenoside compound K inhibited the proliferation, migration, and invasion of Eca109 cells through the VEGFA/Pi3k/Akt pathway [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The phosphorylation patterns of related molecules differ among patients. This suggests that different tissue microenvironments affect the expression of PD-L1, it is essential to design appropriate PD-1 blockade combination therapy regimens for each patient during any treatment and research programs [ 78 ].…”
Section: Post-translational Modifications (Ptms) Regulate the Pd-1/pd...mentioning
confidence: 99%